2015
DOI: 10.1002/jbio.201500114
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle uptake by macrophages in vulnerable plaques for atherosclerosis diagnosis

Abstract: The composition of atherosclerotic (AS) plaques is crucial concerning rupture, thrombosis and clinical events. Two plaque types are distinguished: stable and vulnerable plaques. Vulnerable plaques are rich in inflammatory cells, mostly only M1 macrophages, and are highly susceptible to rupture. These plaques represent a high risk particularly with the standard invasive diagnosis by coronary angiography. So far there are no non‐invasive low‐risk clinical approaches available to detect and distinguish AS plaque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 116 publications
0
18
0
Order By: Relevance
“…Optical techniques are often focused on investigating the composition and vulnerability of plaques (20)(21)(22). But for the characterization of early plaque development, the cellular level of lipid metabolism is also of foremost interest.…”
mentioning
confidence: 99%
“…Optical techniques are often focused on investigating the composition and vulnerability of plaques (20)(21)(22). But for the characterization of early plaque development, the cellular level of lipid metabolism is also of foremost interest.…”
mentioning
confidence: 99%
“…Rod-shaped GNPs were used, with a spectral peak of 660 nm [17,18]. The GNPs were conjugated to two different anti-EGFR antibodies: a recombinant human/mouse chimeric EGFR monoclonal antibody [Cetuximab (Erbitux), Merck KGaA, Germany] and an affinity purified rabbit polyclonal antibody (PDGFR-α, Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Immunostainingmentioning
confidence: 99%
“…between chromosome 7 polysomy and GBM prognosis, and findings in the literature for the prognostic significance of EGFR overexpression are contradictory. One study suggested that it is indicative of poorer outcome [19] but others failed to support this conclusion [5,17,18,22], except in pediatric GBM, in which overexpression of EGFR was linked to a worse prognosis [23].…”
Section: Egfr Overexpression In Gbmmentioning
confidence: 99%
“…2,11 After MΦ differentiation, the cells were loaded with GNP. The MΦ were incubated with the GNS or GNR at 37°C (95% humidity) for 24 hours in Roswell Park Memorial Institute medium.…”
Section: Preparation Of Mφ and Gnp Loadingmentioning
confidence: 99%
“…2 On the molecular level, a specific molecular or cellular target is required that is specifically expressed between stable and vulnerable plaques. 5 Many noninvasive techniques are commonly used for molecular detection purposes.…”
mentioning
confidence: 99%